Factors influencing halal food purchasing behavior among Thai Muslim in five southern border provinces - Bunnag, Saranya (2013)
This survey research was aimed to determine the factors that influence arid are associated with food purchasing behavior among Thai Muslim consumers based on the halal logo on food products.Using multi-stage sampling technique, the subjects of this study were 1,000 Thais Muslim living in 5 southern border provinces.They were interviewed by a questionnaire between March and May, 2009.The results of this research showed that with regard to knowledge of the true definition of halal, 85% expressed that it was extremely concerned with religious belief.Seventy-two percent mentioned that halal food was substantially related to food safety.Fifty-four percent cited that halal food was considerably involved with environmental friendly products. Fifty-seven percent stated that halal food was exceedingly about not to torture animals.The logos that the subjects saw and recognized the most was the halal logo of Thailand, Malaysia, Singapore, China, Indonesia, America, France, and Australia, respectively.When buying meat, sea food, fruits and vegetables, the logos that the subjects had the most trust and confidence in was the halal logo of Malaysia,Thailand, and Indonesia, respectively.In addition. based on the statistically significant coefficients by using logistic regression analysis, it was found that factors influencing the deviation of behavior in choosing halal hod were gender, household income per month, labels indicated source of production, and labels certified products as halal food, product quality, price, sale promotion, and selling place.